Analysis of Land Use Changes and Their Impact on Environmental Quality in Kembaran Subdistrict (2016–2022) - Akilah, Fitrian Bilqist; Junarto, Rohmat; Suharno, Suharno (Sekolah Tinggi Pertanahan Nasional, 2024)
The conversion of agricultural land to non-agricultural use in Kembaran District, prompted by the development of Purwokerto, has resulted in multiple environmental impacts. This study seeks to analyze land changes and their effects on environmental quality from 2016 to 2022, employing a mixed-methods approach that integrates both quantitative and qualitative data within a spatial framework. The analysis identifies six categories of land use changes. Mixed Gardens are transformed into Rare Villages (1,954 ha) and Rare Housing (0.156 ha); Irrigated Rice Fields are converted into Small Industries (5,838 ha), Road Networks (0.270 ha), Rare Villages (3,374 ha), and Sparse Housing (2,642 ha). The alterations impact the quality of the residential environment, categorized into good (131,758 ha), medium (311,003 ha), and poor (310,903 ha) classifications. High-quality settlements exhibit low to medium density, abundant shade trees, and significant distance from pollution sources. In contrast, the medium category is characterized by medium density and a moderate presence of shade trees. Poor-quality settlements exhibit high density, a scarcity of shade trees, and closeness to pollution sources. The findings indicate that agricultural land conversion diminishes productive land and exacerbates environmental quality, particularly in densely populated areas with limited vegetation and proximity to pollution sources.